Assessment of the environmental sustainability of plant-based meat and pork: Opportunities for improved sustainability practices in the industry - Emery, Issac (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented by Issac Emery, Informed Sustainability Consulting, on 29 June 2021 at the second day of the Asian Development Bank (ADB) Webinar on Sustainable Protein Case Study: Outputs and Synthesis of Results.